Optimization of on‐line hydrogen stable isotope ratio measurements of halogen‐ and sulfur‐bearing organic compounds using elemental analyzer–chromium/high‐temperature conversion isotope ratio mass spectrometry (EA‐Cr/HTC‐IRMS). (9th February 2017) - Gehre, Matthias; Renpenning, Julian; Geilmann, Heike; Qi, Haiping; Coplen, Tyler B.; Kümmel, Steffen; Ivdra, Natalija; Brand, Willi A.; Schimmelmann, Arndt
Abstract : Rationale: Accurate hydrogen isotopic analysis of halogen‐ and sulfur‐bearing organics has not been possible with traditional high‐temperature conversion (HTC) because the formation of hydrogen‐bearing reaction products other than molecular hydrogen (H2 ) is responsible for non‐quantitative H2 yields and possible hydrogen isotopic fractionation. Our previously introduced, new chromium‐based EA‐Cr/HTC‐IRMS (Elemental Analyzer–Chromium/High‐Temperature Conversion Isotope Ratio Mass Spectrometry) technique focused primarily on nitrogen‐bearing compounds. Several technical and analytical issues concerning halogen‐ and sulfur‐bearing samples, however, remained unresolved and required further refinement of the reactor systems. Methods: The EA‐Cr/HTC reactor was substantially modified for the conversion of halogen‐ and sulfur‐bearing samples. The performance of the novel conversion setup for solid and liquid samples was monitored and optimized using a simultaneously operating dual‐detection system of IRMS and ion trap MS. The method with several variants in the reactor, including the addition of manganese metal chips, was evaluated in three laboratories using EA‐Cr/HTC‐IRMS (on‐line method) and compared with traditional uranium‐reduction‐based conversion combined with manual dual‐inlet IRMS analysis (off‐line method) in one laboratory. Results: The modified EA‐Cr/HTC reactor setup showed an overall H2 ‐recovery of more than 96% for all halogen‐ and sulfur‐bearing organic compounds. All results were successfully normalized via two‐point calibration with VSMOW‐SLAP reference waters. Precise and accurate hydrogen isotopic analysis was achieved for a variety of organics containing F‐, Cl‐, Br‐, I‐, and S‐bearing heteroelements. The robust nature of the on‐line EA‐Cr/HTC technique was demonstrated by a series of 196 consecutive measurements with a single reactor filling. Conclusions: The optimized EA‐Cr/HTC reactor design can be implemented in existing analytical equipment using commercially available material and is universally applicable for both heteroelement‐bearing and heteroelement‐free organic‐compound classes. The sensitivity and simplicity of the on‐line EA‐Cr/HTC‐IRMS technique provide a much needed tool for routine hydrogen‐isotope source tracing of organic contaminants in the environment. Copyright © 2016 John Wiley & Sons, Ltd.